The mechanical behaviour of weathered granitic rock slope by wetting and drying cycle / Ummi Khadijah Shamsuddin - Shamsuddin, Ummi Khadijah (2018)
Geological Engineering is concerned with the identifying and understanding the geological controls on the engineering properties. These control range can come from the properties of the rock such as the capacity of materials to hold fluids, and boundaries within a volume. The main aim of rock mechanics is to understand the behaviour of the rock and be able to predict the how they will response when there is weathering agent contact and force acting on them. There are many factors that will make the strength of rock reduce. One of the most influence factor that will reduce the strength is weathering process. When weathering process take place some of the minerals that make the rock strength may be altered. Simulation of weathering process have been conducted by laboratory testing to investigated the changes to the rock for physical; porosity of the rock sample and the mechanical properties especially for the compression strength of the rock. The relationship between weathering and properties of rock; physical, dynamic and mechanical has been identified and there is some changes occur due to the weathering process.